STUDENTS' UNDERSTANDING OF ELEMENTARY SCHOOL TEACHING MODULES - Naeli Nur Hidayah; Samsiatun Nisa; Nur Fatmawati; Muhamad Anis Afiqi; Umi Zulfa (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2023)
This research aims to measure the level of understanding of PGSD students regarding elementary school teaching modules. The teaching module is part of the material in the Elementary Learning Design course. This research includes descriptive quantitative research. Data was collected using a questionnaire and analyzed using SPSS. The research results show that the level of understanding of elementary school teaching modules among students is moderate. This will have to be a matter of concern and as evaluation material to make improvements in preparing students regarding the knowledge and skills in preparing elementary school teaching modules so that they are better prepared to carry out Teacher Training PPL and work in schools.